ANALISIS PERKAWINAN BEDA AGAMA DALAM PRESPEKTIF RELIGIUSITAS DAN AKIBAT HUKUMNYA - DEWI, MIEKE ANGGRAENI (Universitas Mahasaraswati K. Mataram, 2023)
In the reality of community life, marriage appears to be relatively straightforward when both couples share the same religious beliefs. However, issues arise when the couple holds differing religious convictions. These religious differences can impede the execution of a marriage. This research employs a juridical-normative method, which involves an approach that examines legal regulations and other relevant provisions related to interfaith marriages. The regulations explored in this research pertain to interfaith marriages. The legal consequences of an interfaith marriage are that the marriage is not recognized as valid according to the respective religious beliefs of the individuals involved. Therefore, from a legal standpoint, this marriage is also deemed invalid according to the Marriage Law No. 1 of 1974. The result of an invalid marriage also impacts the status and position of children born from an interfaith marriage. Children born from interfaith marriages are considered born out of wedlock, as the marriage of their parents is not recognized as valid. Consequently, these children only have legal relations with their mothers and not with their fathers.